Examining How Media Literacy and Personality Factors Predict Skepticism Toward Alcohol Advertising. Issue 5 (3rd May 2016) - Austin, Erica Weintraub; Muldrow, Adrienne; Austin, Bruce W.
Abstract : To examine the potential effectiveness of media literacy education in the context of well-established personality factors, a survey of 472 young adults, focused on the issue of alcohol marketing messages, examined how individual differences in personality associate with constructs representing aspects of media literacy. The results showed that need for cognition predicted social expectancies and wishful identification with media portrayals in alcohol advertising only through critical thinking about media sources and media content, which are foci of media literacy education. Need for affect did not associate with increased or diminished levels of critical thinking. Critical thinking about sources and messages affected skepticism, represented by expectancies through wishful identification, consistent with the message interpretation process model. The results support the view that critical thinking about media sources is an important precursor to critical thinking about media messages. The results also suggest that critical thinking about media (i.e., media literacy) reflects more than personality characteristics and can affect wishful identification with role models observed in media, which appears to be a key influence on decision making. This adds support to the view that media literacy education can improve decision making across personality types regarding alcohol use by decreasing the potential influence of alcohol marketing messages.